Comparing recent changes in the Arctic and the Third Pole: linking science and policy. (3rd July 2022) - Fernandes, Michelle; Rasouli, Kabir; Golubkin, Pavel; Dolatshah, Azam; Radchenko, Iuliia; Prokhorova, Uliana; Dixit, Abhilasha; Prakash, Akhil E.; Arunkarthik, Arun; Acharya, Asutosh; Senapati, Balaji; Nela, Balaraju; et al.
ABSTRACT: The rapid evolution of science compels renewal of a knowledge-based policy, particularly in cold regions. In the Arctic and Himalayas, which have undergone a significant climate change, there is a disconnect between scientific knowledge and the practices of policy. The rising air temperatures, decreasing ice and snow, increasing precipitation and plastic waste pollutants and the Atlantification of the Arctic Ocean by receiving warmer and saltier water from the Atlantic Ocean call for scientific research questions to strengthen the linkage between science and policy. The Arctic amplification can have remote impacts on other parts of the globe through oceanic and atmospheric teleconnections. Hence, researchers need to push the frontiers of scientific discoveries through multidisciplinary and collaborative approaches in the Arctic Ocean along with connections to the Third Pole – Himalayas. The overall objectives of this paper are to explore how a comparison of the Arctic and the Third Pole is valuable for understanding the Arctic and global biogeophysical processes in this epoch of anthropogenic climate change; provide a strong linkage between the Arctic scientific research and its relevance to society; and help advance a more sustainable future for the Arctic, the Third Pole and the globe.